Defatted coconut residue polysaccharides as potential prebiotics: study of their effects on proliferation and acidifying activity of probiotics in vitro - Marikkar, Mohammed Nazrim (Springer, 2016)
This research aims to extract and characterize polysaccharides from defatted coconut residue (DCR) and determine their potential use as prebiotic. The extraction of the polysaccharides has yielded about 0.73 ± 0.04%. The polysaccharides have been characterised the monosaccharide composition using HPLC-RI and β-glycosidic bond assessment using FTIR. The presence of β-glycosidic bond in DCR has been confirmed by the presence of peak around 893 cm-1. Result showed that the polysaccharides contain about 6.95% of total carbohydrate and 20.71% of reducing sugar. Prebiotic potential of the polysaccharides was determined by using the polysaccharides as carbon source in the basal medium. The plate count results showed, there was a significant increase in the Lactobacillus casei Shirota strain and it was comparable to commercial Inulin. They also suppressed the growth of E.coli ATCC 1129. It can be concluded that polysaccharides from coconut waste can be a good alternatives for prebiotic sources in the future.